Brazilian tropical dry forest (Caatinga) in the spotlight: an overview of species of Aspergillus, Penicillium and Talaromyces (Eurotiales) and the description of P. vascosobrinhous sp. nov - Barbosa, Renan do Nascimento; Bezerra, Jadson Diogo Pereira; Santos, Ana Carla da Silva; Melo, Roger Fagner Ribeiro; Houbraken, Jos; Oliveira, Neiva Tinti; Souza-Motta, Cristina Maria de (Acta Botânica Brasílica, 2020)
ABSTRACT A literature-based checklist of species of Aspergillus, Penicillium, and Talaromyces recorded in the Brazilian tropical dry forest (Caatinga), the largest tropical dry forest region in South America, is provided. A total of 130 species (60 Aspergillus, 57 Penicillium, and 13 Talaromyces) are reported. Soil was the most common substrate, with 122 species records. Various reported species are well known in biotechnological processes. This checklist reflects the limited knowledge of fungal species in tropical dry environments. These data provide a good starting point for biogeographical studies on species of Aspergillus, Penicillium, and Talaromyces in dry environments worldwide. In addition, the new species Penicillium vascosobrinhous is introduced, an endophytic fungus isolated from cactus of the Caatinga forest in Brazil.